SYNTHESIZING GRAMMAR AND STRUCTURE PROBLEMS FACED BY INDONESIAN TOEFL PARTICIPANTS - Hampp, Paula L; Kumayas, Tirza A; Lengkoan, Fergina (Universitas Pendidikan Ganesha, 2021)
The TOEFL test is one of the requirements to pass the Thesis exam at several universities in Indonesia. Grammar and Structure Score is the lowest score, and it becomes a problem for the test takers. This study aimed to analyze the factors of Grammar Structure difficulties experienced by students in solving TOEFL questions. This research approach is descriptive qualitative with a sample of 20 students and taken by purposive sampling of 70 students. Interviews and questionnaires were conducted as a data collection tool. The results showed that there were several problems which were factors that influenced the TOEFL participants' written structure and expression lower than listening and reading scores. They cannot analyze the wrong words in part B. A lack of practice on grammar causes problems, and students study independently without guidance and instruction from lecturers or experts. That four main factors cause students to have difficulty solving TOEFL questions: not preparing for the exam, lack of grammar practice, lack of vocabulary mastery, and learning independence. In this case, students and teachers have responsibility for learning achievement, even if these factors come from the TOEFL takers themselves.